NORTH SOUTH ASYMMETRY IN THE IONOSPHERIC EQUATORIAL ANOMALY IN THE AFRICAN AND THE WEST ASIAN REGIONS PRODUCED BY ASYMMETRICAL THERMOSPHERIC WINDS - AYDOGDU, M (Pergamon-Elsevier Science Ltd, 1988)
[Abstract Not Available]